Improving Mathematical Reasoning Ability with an Integrated Scientific Approach to the Problem Solving Model for Class X Students of Bina Bersaudara Private High School Medan - Yosua Tumanggor; Erlinawaty Simanjuntak (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to improve students' mathematical reasoning abilities through the Integrated Problem Solving learning model in a scientific approach with the help of geogebra for class X students of SMA Bina Bersaudara Medan. The subjects in this study were 47 students of X-MIA class at Bina Bersaudara Private High School Medan. From the initial ability test, it was obtained that the average score of students was 2.41 which was included in the low category and 42.55% who completed. After being given action in cycle I and given a mathematical reasoning ability test, it was obtained that the average score of 2.79 students was included in the moderate category (53.19%) who passed. In cycle I, the percentage of completeness of mathematical reasoning had not been achieved, so cycle II was carried out. After being given action in cycle II and given a mathematical reasoning ability test, an average score of 3.03 was obtained in the good category and 87.23% had completed. From cycle I to cycle II, an increase in the average score and the percentage of mathematical reasoning completeness were obtained.